2017
DOI: 10.1021/acs.nanolett.7b01994
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Effects on Phase Separation

Abstract: Classical nucleation theory predicts that a binary system which is immiscible in the bulk should become miscible at the nanoscale when lowering its size below a critical size. Here we tackle the problem of miscibility in nanoalloys with a combination of ab initio and atomistic calculations, developing a statistical-mechanics approach for the free energy cost of forming phase-separated aggregates. We apply it to the controversial case of AuCo nanoalloys. AuCo is immiscible in the bulk, but a rich variety of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 39 publications
11
64
0
Order By: Relevance
“…This is effect becomes nonnegligible for very small nanoparticles (~2-3 nm in size) i.e. clusters [82][83][84]. The large curvature of small nanoparticles is responsible of the strain which gives a volume contribution into the excess Gibbs energy of nanoparticles.…”
Section: Phase Diagrams Of Npsmentioning
confidence: 99%
“…This is effect becomes nonnegligible for very small nanoparticles (~2-3 nm in size) i.e. clusters [82][83][84]. The large curvature of small nanoparticles is responsible of the strain which gives a volume contribution into the excess Gibbs energy of nanoparticles.…”
Section: Phase Diagrams Of Npsmentioning
confidence: 99%
“…Hence, in early GO studies of clusters, generally only empirical (or semi-empirical) potentials (EP) were used [58][59][60][61][62][63][64][65][66]. Even today, many studies employ this EP-GO approach, which is usually followed by geometry refinement with more rigorous first principle methods [67][68][69][70][71][72][73][74][75][76][77][78][79]. The main advantage of this approach is that it can also be applied to large clusters, of several hundreds or a few thousands of atoms.…”
Section: Global Optimization Methods For Metal Clusters and Nanoalloysmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Many new properties have been then discovered such as the giant diffusion of liquids, [16][17][18] the apparition of new phases and new transitions, [19][20][21][22] giant dielectric properties, 11,12,[23][24][25] the increase of optical properties, 26 and the possible mixing of non-miscible mixtures. 27 These observations indicated that the classical understanding of the physics of liquids should be revisited in confined geometry. Whereas these effects have been largely investigated in the case of confined single components [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and immiscible binary mixtures, [28][29][30] less works have been devoted to the confinement of miscible liquid mixtures.…”
Section: Introductionmentioning
confidence: 99%